A 7,000 years trajectory of socio-ecosystems in the montane belt of the northern French Alps - Julien, Andréa; Messager, Erwan; Doyen, Elise; Etienne, David; Marquer, Laurent; Giguet-Covex, Charline (Frontiers in Environmental Archaeology, 2025)
IntroductionThis study, conducted on the Plateau des Glières, in the northern French Alps, investigates the evolution of vegetation composition over the past 7000 years. This site, within a montane ecosystem, offers a new opportunity to understand the human and landscape interactions under the influence of climate. To study these interactions as a whole and by integrating their complexity, we used two conceptual frameworks: the agroecosystem and the trajectory.MethodsThe analyses conducted are based on a detailed analysis of pollen, NPP, macro-charcoal, and geochemical data from peat cores.ResultsThe vegetation history of the Plateau des Glières is dominated by forest, due to its location within the montane belt (1,435 m). However, the vegetation composition trajectory of the Glières reveals three regimes: two are characterized by an evolutionary trend of the system, and between them, the a third regime is characterized by a “dynamic steady state” of the system. The first regime, corresponding to the Neolithic period, is initially characterized by a closed forested environment with a progressive trend toward a more open landscape due to the first agro-pastoral activities. The second regime is recorded from the very end of the Neolithic until the High Roman Empire. It corresponds to a relatively stationary system, characterized by the progressive development of pastoral activities leading to low impacts on the landscape. This long period (4300 to 1800 cal. BP) is characterized by the sustainability of the agroecosystem that developed. After this long pseudo-stable phase, a tipping point in the vegetation composition trajectory is highlighted. The third regime, spanning from the Migration Period to the present day, is the result of the intensification and diversification of agro-pastoral activities (pastoralism, cereal crops, and fruit trees). The landscape that we can see today in the Plateau des Glières is the legacy of this trajectory characterizing the interactions between ecosystems and human societies, i.e., the socio-ecosystem.DiscussionWhile the agroecosystem trajectory reconstructed on the Plateau des Glières is rather consistent with the altitudinal model of anthropization previously proposed for this region, the vegetation response to the activities is unusual because it shows a long phase of ecosystem stability despite the relatively high human pressure.